Weighing the predictors: host traits and coinfecting species both explain variation in parasitism of Rock Ptarmigan. Issue 8 (5th August 2021) - Morrill, André; Nielsen, Ó. K.; Stenkewitz, U.; Pálsdóttir, G. R.; Forbes, M. R.; Skírnisson, K.
Abstract: Testing hypotheses in ecological and evolutionary parasitology can require testing whether host traits or coinfecting parasites explain variation in parasitism by focal species. However, when host traits and coinfecting parasites are considered separately, relations between either and parasitism by focal species can be spurious—a problem that is addressed when both are considered together. We assessed whether abundances of focal parasites related to host age/sex and coinfecting parasites for three endoparasites and nine ectoparasites of Icelandic Rock Ptarmigan ( Lagopus muta ) collected over 12 yr (2006–2017), and quantified the variation in focal parasitism explained by these predictors. Host traits and coinfecting parasites explained significant variation in abundance of all nine focal parasite species for which models converged, when those models were based on groups of parasites sharing tissue tropism and/or transmission pathways and included year as a random effect. We found a single spurious relation: a host age–sex interaction effect that was removed once concurrent parasitism was considered. When considering focal parasites within groups of coinfecting parasites, we found cases of positive, negative, and lacks of correlations. The amount of variation in focal parasite abundance explained by host traits versus coinfecting parasites depended on the focal parasite and its group. Overall variation explained was both related to the prevalence of the focal parasite, possibly due to underlying parasite aggregation, and similar to variation explained in other models in ecology and evolution. We conclude that host traits and coinfecting parasites often combine to determine infection by focal species. Future studies should also explore the mechanisms underlying parasite–parasite relations and their potential impacts on host demography for this and other study associations, and assess relative effects of host traits and coinfecting parasites on focal parasitism.